Óleo de canola e selênio orgânico para codornas de duplo propósito - Roll, Aline Arassiana Piccini (2012)
Recent results suggest that the supplementation of quail breeders with organic selenium2 and canola oil could improve their performance and egg quality and of their progenies too, To test this hypothesis two trials were conducted, In the first, breeders (252 females and 72 males) were fed throughout a period of 110 days with six treatments, that consisted on a completely or partial substitution of soybean oil (SO) by canola oil (CO) with or without organic selenium (Se) supplementation, The birds were allocated in a completely randomized design in a factorial 3 x 2 (three levels of canola oil: 0, 50 and 100% of substitution by SO) and two level of organic Selenium supplementation (0 and 0,3 ppm). The variables analyzed were quails performance, egg quality, egg shelf life, egg fatty acid profile and some carcass traits of males. In the second trial a total of 344 eggs from 252 quails fed the experimental diets during 90 days were incubated, Later, egg weight, egg production, and body weight from the first generation offspring were evaluated. A basal corn-soybean meal diet of the progeny was the same to all birds and was formulated to contain 22% crude protein and 2,780 kcal of metabolizable energy. A total of 167 female s quails were hatched and their performance during the initial laying cycle (up to 63 days of age) was evaluated. Correlation analysis and regression equations were used to estimate the effects of quail age on carcass traits of the males. Treatment means were compared by orthogonal contrasts and Duncan s test at 5% level. By contrast analysis, it was observed that total or partial substitution of SO by CO had no effect on quails performance (P>0,05). The Se increased the left testicle weight, decreased abdominal fat and breast weight when supplemented on CO (P=0,01). The inclusion of CO on diet, when not supplemented with Se impaired the ¨Haugh¨ unit at 21 days of storage (P=0,02). The substitution of SO by CO changed the fatty acid profile in yolk, increasing the percentage of oleic and decreasing linoleic, regardless of Se supplementation (P=0,01). Breeders that were supplemented with Se produced chicks heavier than birds that were not supplemented (10,27 vs 9,97) regardless of the oil used in the diet (P=0,055). Progeny from breeders fed with Se produced heavier eggs (12,34 vs 11,94) than from birds not supplemented (P=0,038). Egg production and egg mass of the progeny were not significantly affected by nutritional treatments of the breeders. In conclusion the canola oil diet and organic selenium supplementation brought about benefits for the breeders and the first progeny of quails. The inclusion of CO changes positively the fatty acid profile in egg yolk.